2014
DOI: 10.1002/bip.22467
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and EPR characterization of rigid, 310‐helical peptides with TOAC spin labels: Models for short distances

Abstract: For 3D-structure determination in biophysical systems EPR is rapidly gaining ground. Proteins labeled specifically with two nitroxide spin labels can be prepared, and several EPR methods are available for distance determination, which makes it possible to determine distance constraints. However, such methods require frozen solutions, potentially causing non-physiological states of the sample. Here, we target spin- spin interaction in liquid solution at room temperature using rigid model compounds. A series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…The DFT geometry optimization procedure has led to a 3 10 -helical structure for all of the peptides studied in this work, consistent with previous theoretical and experimental studies. 3 5 For the systems OCTA 2,7 and NONA 2,8 we have found that the principal values of the hyperfine tensors ( A 1 and A 2 ) are equal.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The DFT geometry optimization procedure has led to a 3 10 -helical structure for all of the peptides studied in this work, consistent with previous theoretical and experimental studies. 3 5 For the systems OCTA 2,7 and NONA 2,8 we have found that the principal values of the hyperfine tensors ( A 1 and A 2 ) are equal.…”
Section: Discussionmentioning
confidence: 90%
“…The high fraction of monoradical in HEXA 1,5 seems too high given the chemical purity of the sample and may indicate a dynamic process, as discussed before. 5 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The principal values of the 14 N hyperfine coupling tensor were A xx = A yy = 13 MHz and A zz = 110 MHz. 35 The spectra were simulated with a superposition of three components: a fast fraction using the ''Garlic'' function, a medium and a slow fraction using the ''Chili'' function. For the 9 GHz spectra, a Gaussian component with a linewidth of 0.12 mT was used for the fast component, and 1 mT for the medium and slow components.…”
Section: Simulations Of Epr Spectramentioning
confidence: 99%